Study on Safety of Navigation using Automatic Identification System for Marine Traffic Area Case Study: Malacca Straits - Muhammad Badrus Zaman (International Journal of Marine Engineering Innovation and Research, 2016)
International Maritime Organization (IMO) has recommended the implementation of Automatic Identification System (AIS) to improve the safety of navigation at marine traffic area. Based on regulation, IMO requires AIS to be fitted aboard all ships of 300 gross tonnage and upwards engaged on international voyages, cargo ships of 500 gross tonnage and upwards not engaged on international voyages and all passenger ships irrespective of size. The function of the AIS is to make communication between ship to ship and communication between ship to the port or land area. In this study, the study area is the Malacca Strait. Malacca Straits is the strait categorized as high risk level. Malacca straits is also busy area for maritime transportation because it is an area for international transportation lines. Many captains feel anxious and cautiously when passes through the strait. AIS receiver was used in this study which has been installed at Universiti Teknologi Malaysia by Kobe University Japan. Using AIS receiver, the current condition of the ship in the Malacca Straits area can be monitored properly. In addition, the data recorded on the AIS receiver can be used for research to enhance safety of navigation.